Effect of fatigue on single-leg hop landing biomechanics - Orishimo, K. F.; Kremenic, I. J. (Journal of Applied Biomechanics, 2006)
The objective of this study was to measure adaptations in landing strategy during single-leg hops following thigh muscle fatigue. Kinetic, kinematic, and electromyographic data were recorded as thirteen healthy male subjects performed a single-leg hop in both the unfatigued and fatigued states. To sufficiently fatigue the thigh muscles, subjects performed at least two sets of 50 step-ups. Fatigue was assessed by measuring horizontal hopping ability following the protocol. Joint motion and loading, as well as muscle activation patterns, were compared between fatigued and unfatigued conditions. Fatigue significantly increased knee motion (p = 0.012) and shifted the ankle into a more dorsiflexed position (p = 0.029). Hip flexion was also reduced following fatigue (p = 0.042). Peak extension moment tended to decrease at the knee and increase at the ankle and hip (p = 0.014). Ankle plantar flexion moment at the time of peak total support moment increased from 0.8 (N×m)/kg (SD, 0.6 [N×m]/kg) to 1.5 (N×m)/kg (SD, 0.8 [N×m]/kg) (p = 0.006). Decreased knee moment and increased knee flexion during landings following fatigue indicated that the control of knee motion was compromised despite increased activation of the vastus medialis, vastus lateralis, and rectus femoris (p = 0.014, p = 0.014, and p = 0.017, respectively). Performance at the ankle increased to compensate for weakness in the knee musculature and to maintain lower extremity stability during landing. Investigating the biomechanical adaptations that occur in healthy subjects as a result of muscle fatigue may give insight into the compensatory mechanisms and loading patterns occurring in patients with knee pathology. Changes in single-leg hop landing performance could be used to demonstrate functional improvement in patients due to training or physical therapy.